COMPARATIVE STUDY ON MARRIAGE PROMISES IN INDONESIA AND JORDAN IN OVERVIEW OF MASLAHAT - Bunyamin, Mahmudin; Hermanto, Agus; Hidayat, Iman Nur (SMART: Journal of Sharia, Traditon, and Modernity, 2021)
The development of Islamic family law (al-Ahwal al-Syakhshiyah) in modern Islamic countries can be said to be a new format that accommodates the ideas of reforming Islamic law thought, including the position of marriage vows. The new thing in family law can be seen from the transition from fiqh law to positive law in the form of legislation in Muslim countries. Indonesia and Jordan, are one of the few Muslim countries that legalize marriage vows in legislation. The problem is how the form of marriage vows legislation in each of these countries. This study aims to determine the philosophical meaning and model of its renewal in each of these countries. The concept of maslahat that is applied in the legislation on marriage vows in Indonesia and Jordan is the concept of achieving a goal of Islamic law itself,  to achieve a legal benefit and reject harm or with the principle of preserving an existing law or rule that is considered good, and developing it by law, or more beneficial rules. The formation of marriage vows legislation in Indonesia and Jordan cannot be separated from the local wisdom possessed by each of these countries, so that the concept of maslahat applied in marriage covenant legislation in each country has its own characteristics, each country makes taklik talak a promise. marriage that must be obeyed by both parties.Keywords: Comparative, Marriage Promise, Indonesia, Jordan